Effective tactical actions preceding scored throws categorized by weight category in international-level judo competitions - Ito, K.; Takezawa, T.; Hirose, N. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2023)
Background. Many previous studies have been conducted from multiple perspectives with the aim of improving performance to contribute to victory in judo. In recent years, these studies not only investigated the types and numbers of effective throws from official data but also analyzed the performance of throwing techniques including gripping configurations. Problem and aim. The purpose of this study is to clarify the most effective tactical pattern preceding scored throws in judo throwing techniques. Material and Methods. The video of 705 contests became the research target material. Six hundred eighty-five scored throws and gripping techniques preceding the scored throws were analyzed. Chi-square tests were used to verify any association between the independent variables (cross-grip, regrip, grip target, and rotational throw) and the dependent variable (score earned by throwing technique). The most effective pattern was elucidated by creating a flowchart including 36 tactical action patterns. Results. Using a two-handed grip, without using the cross grip and the regrip, gripping the collar and sleeve(s), and then performing a rotational throw was found to be the most effective tactical pattern in many weight categories. In addition, we confirmed the relationship between consecutive tactical steps in two-handed attacks. It became clear that a rotational throw when gripping the collar and the sleeve(s), and a non-rotational throw when gripping the dorsal region with at least one hand were effective. Conclusions. We could obtain data from different perspectives. By associating the multiple data points from different perspectives, coaches can give competitors more focused advice on tactics in each weight category.